Evaluasi Status Kesuburan Tanah untuk Arahan Pengelolaan Kesuburan Tanah di Desa Pajahan, Kecamatan Pupuan, Kabupaten Tabanan - SUSIANTI, FRISKA; ARTHAGAMA, I DEWA MADE; SUPADMA, A.A. NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Evaluation of Soil Fertility Status for Soil Fertility Local Recommendation at  Pajahan Village, Pupuan District of Tabanan Regency Agricultural lands plays an important role in providing human needs for foods. Agricultural lands can provide an optimal agricultural products if its have a good fertility status. This study aims to determine status of soil fertility at Pajahan Village, its whereabouts, the factors that affect soil fertility, and given local recommendations for soil fertility management at Pajahan Village. This study used soil survey and soil analysis methods with parameters of soil fertility status, namely Cation Exchange Capacity (CEC), Base Saturation (BS), C-organic, total-P and total-K based on the Technical Instructions for Evaluation of Soil Fertility (PPT, 1995). Analysis of total- N and pH content were also carried out as supporting data. The results showed that Pajahan Village has two classes of soil fertility status, namely medium (L2, L3, L4) and high status (L1). The limiting factor for soil fertility status at Pajahan Village is total-P content of L2, L3, and L4. Local recommendations for soil fertility management at Pajahan Village is giving a addition of P fertilizer, N fertilizer and also addition of organic fertilizer.